2022
DOI: 10.1007/s10856-022-06677-0
|View full text |Cite
|
Sign up to set email alerts
|

The synergetic effect of pulp chamber extension depth and occlusal thickness on stress distribution of molar endocrowns: a 3-dimensional finite element analysis

Abstract: The aim of this study was to evaluate the effects of butt margin, occlusal thickness and pulp chamber extension depth on stress distributions on mandibular molar endodontically treated teeth (ETT) with EMAX endocrown restoration using 3-dimensional finite element analysis (FEA). The FEA models of endocrown with flat surface or curve surface of butt margin were firstly evaluated stress distributions, and then 9 FEA models of endocrown with 1-, 2- or 3-mm pulp chamber extension depth and 1-, 2- or 3-mm occlusal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…Enamel has a higher modulus of elasticity and therefore serves to support restoration. The more enamel remaining, the more stress it is subjected to and the higher the peak stresses, which is in general agreement with the results of the mechanical study by Mangold and Kern on mandibular premolars [30]. The stress distribution cloud showed that the cervical areas of the different restorations were areas of high stress concentration, which is characteristic of the stress distribution phenomenon in natural teeth.…”
Section: Comparison Of Stress Distribution Of Different Restorations ...supporting
confidence: 88%
“…Enamel has a higher modulus of elasticity and therefore serves to support restoration. The more enamel remaining, the more stress it is subjected to and the higher the peak stresses, which is in general agreement with the results of the mechanical study by Mangold and Kern on mandibular premolars [30]. The stress distribution cloud showed that the cervical areas of the different restorations were areas of high stress concentration, which is characteristic of the stress distribution phenomenon in natural teeth.…”
Section: Comparison Of Stress Distribution Of Different Restorations ...supporting
confidence: 88%
“…The depth of the pulp-chamber extension for the endocrown and the size of the surface area for adhesive retention are directly proportional to the successful transmission of chewing forces to the root. However, a 5 mm extension depth may damage the pulp-chamber floor of the mandibular molar depending on the anatomical conditions (26,27). These results suggest that the stress may intensify in the pulp-chamber extension of the restoration due to chewing force and may result in fracture in the future.…”
Section: Discussionmentioning
confidence: 95%
“…For conventional crowns, a material thickness of 1–2 mm is typical [ 44 , 45 ]. In contrast, endocrowns are characterized by greater thicknesses, generally exceeding 4.0 mm [ 46 , 47 , 48 , 49 ]. This is due to the large combined thickness of the crown (at least 2.0 mm) and pulp chamber extension (over 2 mm), with the overall thickness exceeding 4.0 mm for endocrowns.…”
Section: Discussionmentioning
confidence: 99%